2016
DOI: 10.1097/md.0000000000002818
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in Systemic Lupus Erythematosus

Abstract: The aim of the study was to examine the clinical characteristics and prognosis according to severity of thrombocytopenia and response to treatment for thrombocytopenia in patients with systemic lupus erythematosus (SLE).We retrospectively evaluated 230 SLE patients with thrombocytopenia, and reviewed their clinical data and laboratory findings. Thrombocytopenia was defined as platelet counts under 100,000/mm3, and patients were divided into 3 thrombocytopenia groups according to severity: mild (platelet counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 26 publications
(40 reference statements)
4
27
0
1
Order By: Relevance
“…They revealed that Lgals3 −/− mice naturally developed lupus-like disease by controlling germinal center responses via IFN-γ 17 . In accordance, in the absence of Gal-3, we observed some hematological parameters compatible with SLE, including significant thrombocytopenia 47 . Here, we used a classic model to promote lupus-like disease in mice by pristane 22 .…”
Section: Discussionsupporting
confidence: 86%
“…They revealed that Lgals3 −/− mice naturally developed lupus-like disease by controlling germinal center responses via IFN-γ 17 . In accordance, in the absence of Gal-3, we observed some hematological parameters compatible with SLE, including significant thrombocytopenia 47 . Here, we used a classic model to promote lupus-like disease in mice by pristane 22 .…”
Section: Discussionsupporting
confidence: 86%
“…SLE has many haematological manifestations, including thrombocytopenia. Low platelet count is more frequent in SLE patients than increased platelet number [ 126 ]. It has been associated with other severe symptoms such as kidney injury, haemolytic anaemia, neuropsychiatric manifestations, and a worse course of the disease [ 91 ].…”
Section: Evidence For Platelet Contribution In Autoimmune Disordersmentioning
confidence: 99%
“…The association between thrombocytopenia and characteristics of SLE patients has been investigated in several studies. Thrombocytopenia has been shown to be associated with other severe clinical manifestations and poor prognosis in patients with SLE [68]. However, multicenter data regarding thrombocytopenia in Chinese SLE patients are limited.…”
Section: Introductionmentioning
confidence: 99%